Authorship Trends in Agriculture Research: a Bibliometric Analysis - Krishna, K. M.; Kumar, S. (Journal of Information and Knowledge, 2014)
A case study of citations analysis of 68 doctoral theses on Agriculture and Veterinary Sciences submitted to Rajasthan Agriculture University, Bikaner, during 1996 to 2000 for analysis of subjectwise authorship pattern and trend graph for books and journals is made and reported.